Evaluation of Thimerosal on the Potency and Stability of Inactivated Animal Rabies Vaccine - Ahmadnejad, Farzaneh; Miandehi, Nargess; Gholami, Alireza; Chehrazi, Mohammad; Jodairi Eslami, Saeed; Moradi-Joshaghan, Ali; Parhizkar, Zohreh; Roshanaei, Bahram (Archives of Advances in Biosciences, 2019)
Thimerosal is used as a preservative in Rabies vaccine. This study aimed at comparing potency and stability of inactivated animal rabies vaccine with and without thimerosal. Therefore, two groups of rabies vaccine were produced. The results indicated that thimerosal has no deleterious effect on the vaccine; furthermore, its elimination did not influence the potency and stability of the vaccine.